MENGATASI MALAS BELAJAR MELALUI BEHAVIOR TEKNIK SELF MANAGEMENT PADA SISWA - Muliasetyani, Maulinda Tri; Kiswantoro, Arista; Sumarwiyah, Sumarwiyah (Universitas Muria Kudus, 2023)
The objectives of this study are finding factors that influence learning laziness at SMK N 1 Kalinyamatan and overcoming learning laziness through the application of Behavior Counseling Self-Management Techniques. The type of research is qualitative case study. The data collection techniques are observation, interviews, documentation, and home visits. The results of the study prove that the application of Behavior Self Management techniques in overcoming learning laziness for TAS and AMN can change maladaptive behavior to adaptive behavior. Before counseling, the occurrence of learning laziness in students factor is the financial problems, over tired of working, and often playing game. AMN there are his busy schedule, often over tired hangs out or playing futsal. Therefore, TAS and AMN have learning laziness problems. After individual counseling to a better one, which means that individual counseling using the Behavioristic approach Self Management technique is successfully used to overcome the problem of learning laziness.